Self-reported sleep relates to microstructural hippocampal decline decline in β-amyloid positive adults beyond genetic risk - Grydeland, H; Sederevičius, D; Wang, Y; Bartrés-Faz, D; Bertram, L; Dobricic, V; Düzel, S; Ebmeier, KP; Idland, I-V; Kietzmann, TC; Kievit, R; Kühn, S; et al. (Oxford University Press, 2021)
Study Objectives: A critical role linking sleep with memory decay and β-amyloid (Aβ) accumulation, two markers of Alzheimer’s disease (AD) pathology, may be played by hippocampal integrity. We tested the hypotheses that worse self-reported sleep relates to decline in memory and intra-hippocampal microstructure, including in the presence of Aβ.